Changes in Retinal Oxygen Saturation 1 Month After Femtosecond LASIK Treatment in Chinese Adults with Myopia - Xiaoqi Ma; Shanshan Ge; Xinwei Yang; Yuehua Zhou (Ophthalmology and Therapy)
Abstract Introduction This study aimed to compare changes in retinal oxygen saturation 1 month after femtosecond-assisted laser in situ keratomileusis (FS-LASIK) in Chinese adults with myopia using retinal oximetry. Methods In this prospective, observational, single-center cohort study, Chinese adults aged 18–45 years with myopia were categorized into four groups according to spherical equivalent (SE), with 66 eyes characterized as low myopia (LM −3.00D < SE ≤ −0.50D), 68 eyes as moderate myopia (MM −6.00D < SE ≤ −3.00D), 68 eyes as high myopia (HM −9.00D < SE ≤ −6.00D), and 65 eyes as super-high myopia (SHM: SE ≤ −9.00D). The following were measured before and 1 month after FS-LASIK: SE, intraocular pressure (IOP), average keratometry (Km), and axial length (AL). Other ocular biological parameters included retinal arterial oxygen saturation (SaO2) and retinal venous oxygen saturation (SvO2); parameter difference values are expressed as ∆. Results Of the 267 participants, 63.30% were female and 36.70% were male. The mean SE, AL, SaO2, and SvO2 were −5.93 ± 3.24 D, 26.01 ± 1.35 mm, 93.49% ± 1.67%, and 62.97% ± 4.52%, respectively. Before FS-LASIK, SaO2 was significantly correlated with AL and SE (r s = −0.305, P < 0.001; r s = 0.385, P < 0.001). Significant differences were found in SaO2 across myopia categories (P < 0.001). The changes in the retinal arterial oxygen saturation decreased significantly after FS-LASIK (F = 24.948, P < 0.001). After surgery, SaO2 demonstrated a statistically significant but weak negative relationship with refractive correction (ΔSE) (r s = −0.380, P < 0.001) and axial length (r s = −0.404, P < 0.001), a significant but weak positive correlation with average keratometry cutting value (ΔKm) (r s = 0.354, P < 0.001), and no correlation with the change in IOP (ΔIOP) (P > 0.05). Conclusion Ruling out the influence of refractive error, SaO2 was significantly decreased 1 month after FS-LASIK, while there was no significant change in SvO2. We conjecture that retinal amplification may affect differences in retinal oxygen saturation.